Endeavour. [videorecording (DVD)] The complete third season - Evans, Shaun, 1980-; Allam, Roger; Bradshaw, James (Actor); Dexter, Colin (Masterpiece theatre (Television program), 2016)
Last seen languishing in a prison cell and framed for a crime he didn't commit, Endeavour is compelled to return to duty when a young woman's baffling murder requires his singularly cerebral mind to solve.